Building the Future of the Apparel Industry: The Digital Revolution in Enterprise Architecture - Hindarto, Djarot (Sinkron : jurnal dan penelitian teknik informatika, 2024)
Using qualitative methodology, this study investigates the effects that the digital revolution in corporate architecture has had on the apparel industry. In this article, digital technologies, like AI, big data analytics, and the Internet of Things, are the main points of emphasis. They have revolutionized business and operational practices, as well as marketing strategies in the sector. According to the findings of this study, the implementation of advanced technologies significantly contributes to the enhancement of operational efficiency, the introduction of innovative products, and the enhancement of the competitiveness of businesses. The research also highlights the impact that digital transformation has had on sustainability and personalization in the clothing production industry. It demonstrates that adopting an enterprise architecture that is aligned with digital technologies not only increases operational efficiency but also strengthens innovative and competitive capacity. Furthermore, this research acknowledges the significance of ethically responsible and transparent business practices in this digital era, as well as taking into consideration the effects that digital transformation has on society and the environment. The findings of this study provide industry stakeholders with a strategic perspective that can be utilized in the formulation of adaptive business strategies, the exploitation of opportunities, and the facing of challenges in the ever-changing business environment that is associated with the digital era